Robust Adaptive Fuzzy Control of Chaos in the Permanent Magnet Synchronous Motor - Jinpeng Yu; Junwei Gao; Yumei Ma; Haisheng Yu; Songfeng Pan (Discrete Dynamics in Nature and Society)
An adaptive fuzzy control method is developed to control chaos in the permanent magnet synchronous motor drive system via backstepping. Fuzzy logic systems are used to approximate unknown nonlinearities, and an adaptive backstepping technique is employed to construct controllers. The proposed controller can suppress the chaos of PMSM and track the reference signal successfully. The simulation results illustrate its effectiveness.